2014
DOI: 10.1016/j.ijforecast.2014.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Currency crisis early warning systems: Why they should be dynamic

Abstract: a b s t r a c tTraditionally, financial crisis Early Warning Systems (EWSs) have relied on macroeconomic leading indicators when forecasting the occurrence of such events. This paper extends such discrete-choice EWSs by taking the persistence of the crisis phenomenon into account. The dynamic logit EWS is estimated using an exact maximum likelihood estimation method in both a country-by-country and a panel framework. The forecasting abilities of this model are then scrutinized using an evaluation methodology w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 21 publications
4
64
1
Order By: Relevance
“…In this sense, determination of an optimal cut-off value is crucial since this value discriminates crisis period from calm periods. (Candelon et al, 2013). Thus, using the most appropriate threshold level for a specific Early Warning System model is crucial for the success rate of the model.…”
Section: The Limited Dependent Regression Approachmentioning
confidence: 99%
“…In this sense, determination of an optimal cut-off value is crucial since this value discriminates crisis period from calm periods. (Candelon et al, 2013). Thus, using the most appropriate threshold level for a specific Early Warning System model is crucial for the success rate of the model.…”
Section: The Limited Dependent Regression Approachmentioning
confidence: 99%
“…RR (2011) used univariate and bivariate-logit models while Candelon et al (2010) and Candelon et al (2013) focused their results on multivariate probit models. We show in Section 4 that our results are robust to using logit and probit models and of different dimensions (univariate and multivariate models).…”
Section: Definition Of Variables Used In the Empirical Analysismentioning
confidence: 99%
“…Kaminsky et al (1998) showed that it is possible to find a large number of explanatory variables that may signal the occurrence of a crisis. However, more recently, Candelon et al (2010) and Candelon, Dumitrescu, Hurlin and Palm (2013) showed that univariate and multivariate dynamic probit models present the advantage of yielding plausible results while being fairly parsimoniously parametrized. They found relationships of three types of financial crisis (banking, currency and sovereign debt crisis), but they focused their analysis only from 1985 onwards.…”
Section: Introductionmentioning
confidence: 99%
“…First, we use the exchange rate (ER) pressure index as a proxy for export demand and foreign capital flows shocks. The ER pressure index has been widely used in international finance literature (see Berg / Patillo 1999;Candelon / Dumitrescu / Hurlin 2010;Kaminsky / Lizondo / Reinhart 1998;Sachs / Tornel / Velasco 1996). It is generally defined as a weighted average of percentage changes of policy variables in response to current account or financial account shocks.…”
Section: Introducing Shocksmentioning
confidence: 99%